Cloud Computing Adoption Factors Affecting Academic Performance in UAE Public Universities - Alzaabi , Nouf Mohamed Ibraheem; Wahab, Eta (International Journal of Sustainable Construction Engineering and Technology, 2023)
Cloud computing helps in reducing costs and providing accessibility, reliability, and flexibility especially in educational sector. This able to provide the best educational resources and facilities to all level of students effectively and efficiently. It also seen as a creative technological innovation that provides stable and on-demand access to the available network. Hence, this study aimed to measure the cloud computing adoption factors affecting the academic performance in UAE university. The factors are clustered into five groups namely, knowledge sharing; knowledge application; learnability; perceived self-efficacy; and perceived enjoyment. A questionnaire survey was conducted with the university students to gauge their opinions on the level of significant of each factor affecting the academic performance using 5-points Likert scale. Out of 400 questionnaire sets distributed using random sampling, 382 valid responses were extracted as the collected data. This data was analysed descriptively. The results of the analysis found that that cloud computing adoption factors in perceived self-efficacy group are ranked first in term of its significance in affecting academic performance. The second rank is factors in learnability group; the third is perceived enjoyment; the fourth rank is knowledge application and finally, the fifth rank is knowledge sharing. The impact of this research will be felt simultaneously in the IT and education sectors, particularly through assisting students in utilising cloud computing to store and exchange information for both their academic and personal lives.